An Analysis Of The Cohesion And Coherence In The Ninth Grade Students' Narrative Writings In SMP Negeri 2 Banjar - ., PIPIT OLVA ANDAYANI; ., Prof. Dr.I Ketut Seken,MA; ., Drs. Asril Marjohan,MA (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2014)
Pipit Olva Andayani. 2014. An Analysis Of The Cohesion And Coherence In The Ninth Grade Students? Narrative Writings In SMP Negeri 2 Banjar. Thesis, Department of Language Education, Graduate Program, Ganesha University of Education Thesis. Language Education. Postgraduate Study Program, Ganesha University of Education. Advisors: (I) Prof.Dr.Ketut Seken, M.A, Advisor (II) Dr. Asril Marjohan, M.A This study aimed at describing the cohesion and coherence aspect of English narrative writing created by the ninth grade students of SMP Negeri 2 Banjar. The aims were to describe and explain the problems encountered by the students in their narratives. This study used qualitative research design. The subjects of this study were the ninth grade students of SMP Negeri 2 Banjar in academic year 2013/2014. The obtained data were in the form of scripts of students? narrative writings, responses of the students? questionnaire and script of teachers? interview. The data were analyzed by using the theory of Halliday and Hasan (1976). The findings of the study showed that (1) the cohesion of the narratives was achieved by the use of cohesive devices. Those devices were: reference (personal, demonstrative, comparative), substitution (verbal, clausal), ellipsis (verbal), and conjunction (additive, adversative, causal, temporal), reiteration and collocation (lexical devices). (2) The coherence of the narratives was achieved through the development of themes, and the generic structure. (3) Some problems of coherence identified were the problems with reference (personal, demonstrative), conjunction (additive, adversative, causal, temporal) and limited choice of lexical item. Kata Kunci : cohesion, coherence, narrative Pipit Olva Andayani. 2014. Analisis kohesi dan koherensi tulisan narasi siswa kelas Sembilan SMP Negeri 2 Banjar. Tesis Program Studi Bahasa, Pascasarjana, Universitas Pendidikan Ganesha Tesis. Program Studi Bahasa. Pascasarjana. Universitas Pendidikan Ganesha. Pembimbing (I) Prof.Dr.Ketut Seken,M.A, Pembimbing (II) Dr. Asril Marjohan, M.A Penelitian ini bertujuan untuk menganalisis kohesi dan koherensi pada tulisan narasi yang ditulis oleh siswa kelas IX SMP Negeri 2 Banjar. Penelitian ini juga bertujuan untuk menggambarkan dan menjelaskan masalah-masalah yang ditemukan dalam tulisan narasi siswa. Penelitian ini adalah penelitian kualitatif. Subjek penelitian ini adalah siswa kelas IX SMP Negeri 2 Banjar tahun ajaran 2013/2014. Data diperoleh melalui tulisan narasi siswa, kuisioner siswa dan interview guru. Data yang diperoleh dianalis berdasarkan teori Halliday and Hasan (1976). Temuan pada penelitian ini menunjukkan (1) kohesi dari teks narasi yang diciptakan dengan menggunakan piranti. Piranti tersebut diantaranya; referensi (personal, demonstratif, komparatif), substitusi (verbal, clausal), ellipsis (verbal), konjungsi (penambahan, pertentangan, sebab-akibat, urutan) (piranti grammatical), pengulangan dan kolokasi (piranti leksikal). (2) Koherensi teks narasi diciptakan dengan pengembangan ide utama dari teks itu yang didukung oleh ide setiap paragraph, penggunaan generic structure dari teks narasi. (3) Beberapa masalah dalam koherensi yang diidentifikasi dalam karangan siswa yaitu menyangkut penggunaan referensi (personal, demonstratif), konjungsi (penambahan, pertentangan, sebab-akibat, urutan) dan pemilihan kata dari leksikal item. keyword : kohesi, koherensi dan tulisan narasi